2017
DOI: 10.1016/j.jtherbio.2016.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Long-term and acute effects of temperature and oxygen on metabolism, food intake, growth and heat tolerance in a freshwater gastropod

Abstract: Temperature affects the physiology and life-history of ectothermic animals, often increasing metabolic rate and decreasing body size. Oxygen limitation has been put forward as a mechanism to explain thermal responses of body size and the ability to survive stress. However the time-scales involved in growth performance and heat tolerance differ radically. In order to increase our understanding of oxygen and temperature effects on body size and heat tolerance and the time scale involved, we reared Lymnaea stagna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…We did not find an effect of heat on growth in our experimental design. However, it is likely that, if we had kept the snails under heat treatment for a longer period, we would have detected such a difference (e.g., Leicht et al 2013; Hoefnagel and Verberk 2017; Salo et al 2019). The trend that the snails at 28 °C show might be seen as a confirmation for this previously reported response, and is not surprising given their increased metabolic rate due to the temperature increase.…”
Section: Discussionmentioning
confidence: 96%
“…We did not find an effect of heat on growth in our experimental design. However, it is likely that, if we had kept the snails under heat treatment for a longer period, we would have detected such a difference (e.g., Leicht et al 2013; Hoefnagel and Verberk 2017; Salo et al 2019). The trend that the snails at 28 °C show might be seen as a confirmation for this previously reported response, and is not surprising given their increased metabolic rate due to the temperature increase.…”
Section: Discussionmentioning
confidence: 96%
“…We have not attempted to acclimatize Lymnaea in the laboratory to higher temperatures close to their thermal tolerance upper limit of 30°C (Vaughn, 1953;Salo et al, 2019) and then determine whether the HS has the same effect on LTM formation. Rearing temperature was shown by Hoefnagel and Verberk (2017) not to alter the upper limit of heat tolerance in Lymnaea, and the authors concluded that long-term acclimation had limited capacity to improve heat tolerance. In the freshly collected snails used here, however, although they may experience temperatures greater than 25°C for hours during daytime in summer, that experience does not prevent heat from acting as a stressor.…”
Section: Discussionmentioning
confidence: 98%
“…At present, we cannot determine the reason that L. stagnalis failed to exhibit avoidance behavior in response to the high temperature exposure, however, there are several possible explanations for this. First, the high temperature stressor may not have been recognized as a threat since L. stagnalis has a large range for thermotolerance . Second, the temperature above the water line may not have differed markedly compared to the temperature in the beaker due to the heat of the water bath.…”
Section: Discussionmentioning
confidence: 99%
“…First, the high temperature stressor may not have been recognized as a threat since L. stagnalis has a large range for thermotolerance. 51 Second, the temperature above the water line may not have differed markedly compared to the temperature in the beaker due to the heat of the water bath. Third, increased temperature may have reduced the crawl out behavior if there was a perceived desiccation risk associated with warmer conditions.…”
Section: ■ Discussionmentioning
confidence: 99%